STRATEGI HUMAS DALAM MENSOSIALISASIKAN KEBIJAKAN UMKM PARTAI PERINDO - Ningsih, Cakra (Universitas Prof. Dr. Moestopo (Beragama), 2019)
This study aims to determine the public relations strategy in disseminating the policies of the Perindo Micro Small Medium Enterprises (UMKM). The model used in this study is the Four Steps of Public Relations model and the 7C’s Concept. The paradigm used is post positivism using the case study research method. The public relations strategy in disseminating Perindo UMKM policies is to use mass media such as electronic media, print media, and online media, namely through Facebook, twitter, Instagram and the official Perindo party website at www.partaiperindo.com. In addition, socialization was also carried out by going directly to the field. Constraints faced include; musty credibility, which during the screening was lacking in the research of the Perindo UMKM Public Relations in selecting candidates to be guided by the UMKM program. Besides the aspect of Clarity, the Perindo cart program that is updated on social media is only the end result so that people only see the benefits without knowing the risks. And finally on the Channel aspect, it turns out that there are some who only know the Perindo cart program from electronic media only, not from social media.